Komunikasi dalam Tim Organisasi di Sekolah Dasar Negeri - Kamaludin Kamaludin (UMSU, 2023)
This research aims to establish the communication concept in the organizational team to optimize the performance of Public Elementary Schools. This research uses a qualitative approach with a descriptive type, focusing on analyzing the concept of communication in organizational teams to optimize the performance of Public Elementary Schools. This research was conducted at a Public Elementary School in Wanasari District, Brebes Regency, for four months, from February 2023 to May 2023. The results of this research indicate that communication within the organizational team at Public Elementary Schools is carried out through two communication concepts, namely formal communication and informal communication. Formal communication is structural and procedural communication formulated by Public Elementary Schools. Meanwhile, informal communication is not planned and does not follow the formal structure of public elementary schools but arises from regular social interactions among members of public elementary schools.